7. EEG characteristics in “eyes open” vs “eyes closed” conditions: Small world network architecture in healthy aging and age-related brain degeneration - Miraglia, F.; Vecchio, F.; Rossini, P.M. (Clinical neurophysiology, 2016)
Applying graph theory, we investigated how cortical sources small worldness (SW) of resting EEG in eyes-closed/open (EC/EO) differs in mild cognitive impairment (MCI) and Alzheimer’s disease (AD) subjects respect to normal elderly (Nold). EEGs were recorded in 30 Nold, 30 MCI, 30 AD during EC and EO. Undirected and weighted cortical brain network was built to evaluate graph core measures. eLORETA lagged linear connectivity was used to weight the network. In Nold, EO condition presented more random network (higher SW) in alpha bands and more regular organization (lower SW) in beta2 and gamma bands. In MCI, SW trend was the same, except for delta and theta bands with more ordered organization. AD showed similar trend of Nold, but with less fluctuations between the conditions. Furthermore, in both conditions, MCI SW architecture presented midway properties between AD and Nold. In low frequencies, Nold showed more random network organization, while SW parameter displayed a more ordered architecture with disease progression. Small world properties had different patterns in pathological aging in open eyes, with different trends in EEG frequency bands. Graph theory provides an excellent tool to characterize neuronal network capacities from coupling parameters of time-varying signals.